Critical factors and Benefits in the use of Earned Value Management in construction - Netto, Joaquim Teixeira; de Oliveira, Nylvandir Liberato Fernandes; Freitas, Andrey Pimentel Aleluia; dos Santos, João Alberto Neves (Brazilian Journal of Operations & Production Management, 2020)
Goal: The main objective of this study is to analyze the benefits and the critical success factors (CSF) to use of Earned Value Management (EVM) in the construction projects. Design / Methodology / Approach: The research methodology was quantitative approach with statistical analysis of questionnaire with 106 answered and validated using the Cronbach’s alpha and Kaiser-Meyer-Olkin. Results: The construction companies identified the benefits and CSF in the use of EVM. The observed benefits were: achieving project cost, the definition of scope and schedule, anticipating project and project communication. The observed CSF were: team training, project management maturity, top management support, the need of pre-defined procedures, and the use of appropriate software. Limitations of the investigation: The sample of research was composed exclusively of Brazilian construction managers. Practical implications: Monitoring construction projects using EVM for construction companies. Originality / Value: The EVM is widely used for project management. However, there are few studies on its use in the construction industry.